Assessing the impacts and outcomes of youth driven mental health promotion: A mixed-methods assessment of the Social Networking Action for Resilience study. (August 2018) - Jenkins, Emily K.; Bungay, Vicky; Patterson, Andrew; Saewyc, Elizabeth M.; Johnson, Joy L.
Abstract: Mental health challenges are the leading health issue facing youth globally. To better respond to this health challenge, experts advocate for a population health approach inclusive of mental health promotion; yet this area remains underdeveloped. Further, while there is growing emphasis on youth-engaged research and intervention design, evidence of the outcomes and impacts are lacking. The purpose of this paper is to contribute to addressing these gaps, presenting findings from the Social Networking Action for Resilience (SONAR) study, an exploration of youth-driven mental health promotion in a rural community in British Columbia, Canada. Mixed methods including pre- and post-intervention surveys (n = 175) and qualitative interviews (n = 10) captured the outcomes and impacts of the intervention on indicators of mental health, the relationship between level of engagement and benefit, and community perceptions of impact. Findings demonstrate the feasibility and benefits of youth engaged research and intervention at an individual and community-level.